Population structure and local utilization of spider conch (lambis lambis) in abang island waters, batam - Rentik Nurisma Airani; Yarsi Efendi; Fauziah Syamsi (STKIP Persada Khatulistiwa Sintang, 2026)
This study explores the population structure, spatial distribution, and community utilization of Lambis lambis on Abang Island as a foundation for species conservation and community-based management. The research aims to examine the population structure and distribution patterns of Lambis lambis as well as its utilization by fishing communities on Abang Island, Batam. Data were collected using a 50-meter quadrat transect method with observation plots measuring 5 m × 5 m, along with measurements of environmental parameters (dissolved oxygen, temperature, and salinity). The results indicate low population density (0.012–0.028 ind/m²) and a clustered distribution pattern (Morisita Index > 1). A positive correlation was found between dissolved oxygen and population density, while high temperature showed a negative correlation. These findings suggest that environmental pressure and exploitation influence the spatial distribution of Lambis lambis. This study provides a scientific basis for community-based management and species conservation.